Implementasi ERP SAP HCM Time Management Positive Menggunakan Accelerated SAP(ASAP) Methodology - wuwuh hartiningsih (JUST IT : Jurnal Sistem Informasi, Teknologi Informasi dan Komputer, 2019)
The SAP Activate Methodology is a modular and agile framework for implementation or migration of SAP solutions that provides content and guidance for project teams. ASAP 8 Standard takes a disciplined approach to project management, organizational change management, solution management, and other disciplines applied in the implementation of SAP solutions. The ASAP 8 is built around the SAP Advanced Delivery Management model and supports project teams with templates, tools, questionnaires, and checklists, including guidebooks and accelerators. ASAP 8 empower companies to exploit the power of the accelerated features and tools already built into SAP solutions. SAP HCM Time Management module is part of ERP SAP, so we should using ASAP Methodology while implementing this project.